2017
DOI: 10.1097/cnq.0000000000000154
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Weaning Older Adults From Mechanical Ventilation

Abstract: This study aim was to describe the influences that affect weaning from mechanical ventilation among older adults in the intensive care unit (ICU). Adults older than 65 years comprised only 14.5% of the US population in 2014; however, they accounted up to 45% of all ICU admissions. As this population grows, the number of ICU admissions is expected to increase. One of the most common procedures for hospitalized adults 75 years and older is mechanical ventilation. An integrative review methodology was applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
6
0
2
Order By: Relevance
“…The use of SAPS 3 is able to show scores that infer prognosis beyond 24 hours of admission and reflect the complexity of the care demanded considering the patient’s clinical status ( 32 ) . Other authors ( 20 , 25 , 33 ) also found an association between SAPS 3 and the occurrence of weaning failure, concluding that the SAPS 3 system has a good discriminatory power during the ventilatory weaning process.…”
Section: Discussionmentioning
confidence: 81%
“…The use of SAPS 3 is able to show scores that infer prognosis beyond 24 hours of admission and reflect the complexity of the care demanded considering the patient’s clinical status ( 32 ) . Other authors ( 20 , 25 , 33 ) also found an association between SAPS 3 and the occurrence of weaning failure, concluding that the SAPS 3 system has a good discriminatory power during the ventilatory weaning process.…”
Section: Discussionmentioning
confidence: 81%
“…Patients with prolonged weaning are characterized by evident cardiac and pulmonary comorbidities and/or having undergone severe acute critical illness resulting in long-term ventilation and subsequent muscular weakness [19], as well as impaired fluid balance [20, 21]. The main therapeutic goal is a stepwise reduction of ventilatory support (either by gradually reducing the ventilator’s pressure support or by interrupting the ventilator support on a T-piece trial) and a successive transfer of the patients’ respiratory load [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found a variety of factors are associated with extubation failure, including: (1) demographics and clinical status, such as age, fluid balance, comorbidity burden, cardiac function, mental status, and severity of illness; (2) laboratory abnormalities, such as hypercapnia, serum albumin, and blood urea nitrogen (BUN); (3) respiratory mechanics, such as maximal inspiratory pressure and diaphragmatic function; and (4) treatment interventions, such as sedatives [5,[7][8][9]. However, these predictors are identified from a cluster of diseases including pneumonia, chronic obstructive pulmonary disease, heart failure, and…”
Section: Introductionmentioning
confidence: 99%